Prognositc Significance of Microcystic Elongated and Fragmanted (MELF) Myometrial Invasion Pattern: A Retrospective Study - Oguzhan OKCU; Gokce ASKAN; Bayram SEN; Cigdem OZTURK; Seda DUMAN OZTURK; Gulname FINDIK GUVENDI (Medeniyet Medical Journal)
Objective: Endometrioid endometrial carcinomas (EEC) are the most commonly diagnosed malignancies of the female genital tract. Myometrial invasion depth is one of the most significant pathological prognostic parameters. Different morphological invasion patterns have been characterized. This study aimed to investigate the prognostic significance of the microcystic elongated and fragmented (MELF) myometrium invasion pattern in patients with EEC and its relationship with other clinicopathological parameters. Methods: This study included 101 patients with EEC in our institution between 2011 and 2020. The MELF pattern was evaluated in hematoxylin-eosin-stained sections. Pan-cytokeratin staining was performed on paraffin-embedded blocks of lymph nodes for cases without lymph node metastasis. Results: The MELF pattern was observed in 29 (29.8%) patients. It was significantly associated with lymphovascular invasion (p<0.001), pathologic stage (p=0.048), infiltrative pattern (p<0.001), and necrosis (p=0.005). No significant correlation was observed between the MELF pattern and overall and disease-free survival rates. Conclusions: The MELF pattern is associated with other prognostic parameters, but its prognostic significance for survival has not been found. If the MELF pattern is observed in the hysterectomy material for cases without lymph node dissection during the first surgery, these patients may need additional surgery or adjuvant therapy due to the high risk of lymphovascular invasion and lymph node metastasis.